2021
DOI: 10.1371/journal.pbio.3001491
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression noise in Escherichia coli is condition-dependent and determined by propagation of noise through the regulatory network

Abstract: Although it is well appreciated that gene expression is inherently noisy and that transcriptional noise is encoded in a promoter’s sequence, little is known about the extent to which noise levels of individual promoters vary across growth conditions. Using flow cytometry, we here quantify transcriptional noise in Escherichia coli genome-wide across 8 growth conditions and find that noise levels systematically decrease with growth rate, with a condition-dependent lower bound on noise. Whereas constitutive promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 46 publications
(95 reference statements)
6
41
0
Order By: Relevance
“…That is, GCS causes fast growing cells to stabilize their current state by effectively muting their response to fluctuations in external signals and causes slowly growing cells to become highly sensitive to external signals. This view is consistent with recent work from our lab that shows that gene expression noise in E. coli results to a large extent from the propagation of noise through the gene regulatory network, and that noise levels systematically decrease with growth rate [23]. This suggests a general strategy in which GCS causes slowly growing cells to more actively explore alternative gene expression states and we show elsewhere that such behavior is highly adaptive for bet-hedging strategies [24].…”
Section: Discussionsupporting
confidence: 92%
“…That is, GCS causes fast growing cells to stabilize their current state by effectively muting their response to fluctuations in external signals and causes slowly growing cells to become highly sensitive to external signals. This view is consistent with recent work from our lab that shows that gene expression noise in E. coli results to a large extent from the propagation of noise through the gene regulatory network, and that noise levels systematically decrease with growth rate [23]. This suggests a general strategy in which GCS causes slowly growing cells to more actively explore alternative gene expression states and we show elsewhere that such behavior is highly adaptive for bet-hedging strategies [24].…”
Section: Discussionsupporting
confidence: 92%
“…There is in fact significant evidence supporting that phenotype switching rates tend to decrease with growth rate. In a number of studies it has been observed that gene expression noise levels decrease with growth rate [22][23][24]30] and metabolic heterogeneity has also been observed to increase with nutrient limitation [41][42][43][44][45][46]. Since phenotype switches are often ultimately driven by fluctuations in gene expression or metabolic state [12,[25][26][27][28][29]47], phenotype switching rates will generally increase with gene expression noise levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently not clear what mechanisms underlie the decrease of gene expression noise with growth rate. Analysis of genome-wide noise in E. coli across different growth conditions has shown that while relative noise levels of different genes are highly condition-dependent and are driven by noise propagation through the regulatory network, absolute noise levels decrease systematically with growth rate in a way that appears to affect all genes [24]. This suggests that the overall decrease in gene expression noise with growth rate results from mechanisms that affect all genes.…”
Section: Discussionmentioning
confidence: 99%
“…We did find a single random mutant that shared one of these segregating polymorphisms, and the noise phenotype of this random mutant changed considerably from the progenitor MG1655 in the direction expected if this polymorphism is causal. It has previously been shown that only a small number of genetic changes can affect noise phenotypes (Hornung et al 2012; Metzger et al 2015; Wolf et al 2015; Schmiedel et al 2019; Urchueguía et al 2021; Vlková and Silander 2021).…”
Section: Discussionmentioning
confidence: 99%